Numerical study on the effect of V-notch on the penetration of grounding incidents in stiffened plates - Adietya Berlian Arswendo; Safaraz Muhammad Wildan; Zakki Ahmad Fauzan; Mursid Ocid; Tuswan Tuswan; Iqbal Muhammad (Curved and Layered Structures)
Grounding is an accident on the ship that can hit the bottom ship, propeller, rudder, and other ship structure. Notch is a defect often appearing in ship structures, aircraft structures, bridges, welded joints, and even microstructures. The most formed notch shape is a notch with a V-like shape called a V-notch. The present study relies on the finite element approach to analyze the impact of the V-notch defect on the grounding penetration simulation on a stiffened bottom plate. This study models 28 distinct scenarios distinguished by the quantity, size, and distance between V-notches. Study outputs in reaction force, resistance, and plate deformation due to penetration, stress concentration, and penetration depth of grounding impact on the stiffened bottom plate are obtained using dynamic explicit simulation in the form of penetration. The outcomes of the numerical simulation demonstrate that the existence of V-notch defects causes stress concentration, reducing the plate structure’s resistance and allowable penetration. The plate with one V-notch defect can reduce the resistance to 29.7% of the resistance of the plate without defects. Besides that, the resistance of the plate with two defects drops by only 5.2%, while when there are three defects simultaneously on the stiffener plate, the plate resistance is reduced by 31.4%. This research shows that the number of V-notches does not determine resistance in a plate, but the position of the V-notch on the plate is close to the penetration area, which is about 100 mm from the center of the plate. V-notch defects with smaller opening angles reduce resistance by 34.38% compared to larger opening angles, which only reduce resistance by 29.77%. Therefore, reducing the strength of the ship in grounding will increase the possibility of losing ship buoyancy, cargo leaks, engine and electrical failure, and loss of propulsion.